Protein Expression Er (Estrogen Receptor) in Breast Cancer Degree of Malignancy Mild, Moderate, and Severe - Imam Susilo (Universitas Airlangga, 2012)
Introduction: Mammary carcinoma is the most common malignancy and main mortality cause in women. Hormonal status (ER and PR expression) was long used as patient suitability for hormonal therapy. However, lately there have been many patients with ER and PR negative. This study wanted to prove the relevance of protein expression of ER (estrogen receptor) with the histopathological degree of malignancy of breast invasive ductal cancer and the prognosis of breast cancer with ER protein expression of positive and negative.Methods: In this retrospective and cross sectional analytical study retrieved data about hormonal status (ER expression) and histopathological grading of inﬁltrating ductal carcinoma patients. This study consisted of 201 patients with mammary carcinoma who referred to medical records Department Pathology Anatomic of Faculty Medicine Airlangga University/Dr. Soetomo General Hospital Surabaya on 1 January 2010–31 December 2010 and their medical record suitable with inclusion criterias. The data was categorized into several groups based on the ER expression result.Results: Most of the sample was in 41–50 year age group (37.31%), and 54,7% of them were in poor expression. The relationship of estrogen receptor (ER) with the degree of histopathology inﬁltrating ductal carcinoma patients, obtained p-value = 0.001 (p < 0.5) and the 2 × 2 table is only moderate and severe degrees compared with the results of ER expression results obtained p = 0.001 (p < 0.5) and odds ratio of 0.362 (CI: 0194-0675).Conclusion: This study found signiﬁcant correlation between ER expression with histopathological grading of inﬁltrating ductal carcinoma patients.